2023
DOI: 10.22454/fammed.2023.750371
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Survey Response Rates in Graduate Medical Education Research Studies

Abstract: Background and Objective: Survey response rates of 70% or higher are needed if findings are to be considered generalizable. Unfortunately, survey studies of health professionals have declining response rates. We have conducted survey research with residents and residency directors for over 13 years. Here we describe the strategies we used to obtain optimal response rates in residency training research collaboratives. Methods: We administered over 6,000 surveys between 2007 and 2019 to evaluate the Preparing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Higher response rates may have been achieved by using monetary incentives, multiple recruitment methods, and additional data collection methods, such as paper mailings. 26 Furthermore, the volunteer sampling method used for participant selection may have introduced selection bias, and thus the generalizability of our findings is limited. In addition, although results showed that residents who receive formal or informal training were more comfortable providing adolescent health care and were more likely to conduct time alone with adolescents than those who did not receive training, the specific type of training received was not explored.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Higher response rates may have been achieved by using monetary incentives, multiple recruitment methods, and additional data collection methods, such as paper mailings. 26 Furthermore, the volunteer sampling method used for participant selection may have introduced selection bias, and thus the generalizability of our findings is limited. In addition, although results showed that residents who receive formal or informal training were more comfortable providing adolescent health care and were more likely to conduct time alone with adolescents than those who did not receive training, the specific type of training received was not explored.…”
Section: Discussionmentioning
confidence: 97%
“…This low response rate likely reflects the single recruitment method and electronic strategy. Higher response rates may have been achieved by using monetary incentives, multiple recruitment methods, and additional data collection methods, such as paper mailings 26 . Furthermore, the volunteer sampling method used for participant selection may have introduced selection bias, and thus the generalizability of our findings is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The response rate and demographics of the participants of this study, as shown in the results section above, are comparable to similar large-scale national surveys. 21 …”
Section: Discussionmentioning
confidence: 99%
“…I was eager to read Ericson et al's "Optimizing Survey Response Rates in Graduate Medical Education Research Studies," which described potential strategies to optimize response rates to survey research. 1 Unfortunately, the authors' described strategies are not generalizable because of their highly motivated sample populations. The residency programs involved in the Preparing the Personal Physician for Practice and Length of Training Pilot studies went through rigorous application processes to participate and fully understood the expectations for studying their experience.…”
Section: To the Editormentioning
confidence: 99%
“…Survey response rates in medical education research have steadily declined. 1 Despite this decline, though, the three highest-impact journals for medical education (Academic Medicine, Medical Education, and Advances in Health Sciences Education) do not require a minimum survey response rate in studies submitted for publication. 2 This lack of a requirement may stem from prior research suggesting that response rate does not inversely correlate with nonresponse bias and that justification of the target population sample better determines the relevance of the data.…”
Section: To the Editormentioning
confidence: 99%